Personalized transcranial alternating current stimulation improves sleep quality: Initial findings - Ayanampudi, V.; Kumar, V.; Krishnan, A.; Walker, M. P.; Ivry, R. B.; Knight, R. T.; Gurumoorthy, R. (Frontiers in Human Neuroscience, 2023)
Insufficient sleep is a major health issue. Inadequate sleep is associated with an array of poor health outcomes, including cardiovascular disease, diabetes, obesity, certain forms of cancer, Alzheimer’s disease, depression, anxiety, and suicidality. Given concerns with typical sedative hypnotic drugs for treating sleep difficulties, there is a compelling need for alternative interventions. Here, we report results of a non-invasive electrical brain stimulation approach to optimizing sleep involving transcranial alternating current stimulation (tACS). A total of 25 participants (mean age: 46.3, S.D. ± 12.4, 15 females) were recruited for a null-stimulation controlled (Control condition), within subjects, randomized crossed design, that included two variants of an active condition involving 15 min pre-sleep tACS stimulation. To evaluate the impact on sleep quality, the two active tACS stimulation conditions were designed to modulate sleep-dependent neural activity in the theta/alpha frequency bands, with both stimulation types applied to all subjects in separate sessions. The first tACS condition used a fixed stimulation pattern across all participants, a pattern composed of stimulation at 5 and 10 Hz. The second tACS condition used a personalized stimulation approach with the stimulation frequencies determined by each individual’s peak EEG frequencies in the 4–6 Hz and 9–11 Hz bands. Personalized tACS stimulation increased sleep quantity (duration) by 22 min compared to a Control condition (p = 0.04), and 19 min compared to Fixed tACS stimulation (p = 0.03). Fixed stimulation did not significantly increase sleep duration compared to Control (mean: 3 min; p = 0.75). For sleep onset, the Personalized tACS stimulation resulted in reducing the onset by 28% compared to the Fixed tACS stimulation (6 min faster, p = 0.02). For a Poor Sleep sub-group (n = 13) categorized with Clinical Insomnia and a high insomnia severity, Personalized tACS stimulation improved sleep duration by 33 min compared to Fixed stimulation (p = 0.02), and 30 min compared to Control condition (p < 0.1). Together, these results suggest that Personalized stimulation improves sleep quantity and time taken to fall asleep relative to Control and Fixed stimulation providing motivation for larger-scale trials for Personalized tACS as a sleep therapeutic, including for those with insomnia.